Development of effective biorationals for sustainable management of the invasive South American tomato leafminer Phthorimaea absoluta Meyrick (Lepidoptera: Gelechiidae) - Torto, Baldwyn (University of Pretoria, 2024)
Thesis (PhD (Entomology))--University of Pretoria, 2024.